Morphofunctional evaluation of the testis, duration of spermatogenesis and spermatogenic efficiency in the Japanese fancy mouse (Mus musculus molossinus). Issue 4 (11th July 2017) - Costa, Guilherme M.J.; Leal, Marcelo C.; França, Luiz R.
Summary: Japanese fancy mouse, mini mouse or pet mouse are common names used to refer to strains of mice that present with different colour varieties and coat types. Although many genetic studies that involve spotting phenotype based on the coat have been performed in these mice, there are no reports of quantitative data in the literature regarding testis structure and spermatogenic efficiency. Hence, in this study we researched testis function and spermatogenesis in the adult Japanese fancy mouse. The following values of 68 ± 6 mg and 0.94 ± 0.1% were obtained as mean testis weight and gonadosomatic index, respectively. In comparison with other investigated mice strains, the fancy mouse Leydig cell individual size was much smaller, resulting in higher numbers of these cells per gram of testis. As found for laboratory mice strains, as a result of the development of the acrosomic system, 12 stages of the seminiferous epithelium cycle have been described in this study. The combined frequencies of pre-meiotic and post-meiotic stages were respectively 24% and 64% and very similar to the laboratory mice. The more differentiated germ cell types marked at 1 h or 9 days after tritiated thymidine administration were preleptotene/leptotene and pachytene spermatocytes at the same stage (VIII). The mean duration of one spermatogenic cycle was 8.8 ± 0.01 days and the total length of spermatogenesis lasted 37.8 ± 0.01 days (4.5 cycles). A high number of germ cell apoptosis was evident during meiosis, resulting in lower Sertoli cell and spermatogenic efficiencies, when compared with laboratory mice strains.